2012
DOI: 10.1200/jco.2011.39.2589
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Intrapulmonary Lymph Node Retrieval After Routine Pathologic Examination of Resected Lung Cancer

Abstract: Standard pathology practice frequently leaves large numbers of N1 LNs unexamined, a clinically significant proportion of which harbor metastasis. By improving N1 LN examination, SPE can have an impact on prognosis and adjuvant management. We suggest adoption of the SPE to improve pathologic staging of resected NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
86
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 18 publications
2
86
0
1
Order By: Relevance
“…LN metastasis significantly affects the prognosis of patients with NSCLC (Goya et al, 2005;Ramirez et al, 2012). The difference in 5-year survival between stages I and II is significant.…”
Section: Discussionmentioning
confidence: 99%
“…LN metastasis significantly affects the prognosis of patients with NSCLC (Goya et al, 2005;Ramirez et al, 2012). The difference in 5-year survival between stages I and II is significant.…”
Section: Discussionmentioning
confidence: 99%
“…It often happens that in N1 disease stations 13 and 14 are neglected, leading to disease under staging, and lack of prescription of adjuvant therapy. These may contribute to the observation that some of patients with N0 disease develop early tumor recurrence or distant metastases (8).…”
mentioning
confidence: 99%
“…For intrapulmonary LN or N1, stations 10-12 are usually dissected because they are easily identified and collected; however, the dissection of stations 13-14 is quite difficult and requires adequate training (7). A recent study showed that standard pathology practice frequently omitted to examine 60% of intrapulmonary LNs in 90% of lobectomy specimens, and found unexpected LN metastases in 12 % of reported node-negative patients (8). Nodal metastases affect the classification of the case into N2 or N1 disease, which in turn affects treatment strategies, tumor recurrence, and survival.…”
mentioning
confidence: 99%
“…However, examination of inadvertently discarded intrapulmonary lymph nodes reveals that although 12% of pN0 resections have missed metastasis detectable by H&E staining (14), no patients with H&E-negative lymph nodes (when including the examination of discarded nodes) had IHC positive lymph nodes (Osarogiagbon, Sareen, Wang, et al, unpublished data). This suggests that IHC testing might not overcome the problem of incomplete gross dissection of lymph nodes for routine histologic examination.…”
mentioning
confidence: 99%
“…The thoroughness of hilar and intrapulmonary lymph node examination was not reported in either study. However, judging from a re-analysis of a different trial, ACOSOG Z0030, it was probably suboptimal in both studies, reflecting contemporary pathology practice (13,14).…”
mentioning
confidence: 99%